2016
DOI: 10.1039/c6cc02226j
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular cyclizations of cyclopropenes with indole

Abstract: Novel intramolecular cycloisomerizations of nitrogen-tethered cyclopropenes with indole in the presence of Brønsted acids have been developed. The reactions proceeded through the same pathway but stopped at different stages according to different substituent styles, affording azocino[5,4-b]indole 2 and (epiminoethano)cyclopenta[b]indole 4 in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Shi et al explored the reactivity of gem -diester substituted cyclopropenes 292 containing a pendant indole core on one of the Csp 2 atoms of the strained carbocycle ( Scheme 37 ) [ 114 ]. They uncovered a Lewis acid-catalyzed cycloisomerization reaction which outcome depended on the substitution of the second Csp 2 of the cyclopropene moiety: when it included a H atom azocino[5,4- b ]indoles 293a were obtained, however when it contained an aryl group tetracyclic (epiminoethano)cyclopenta[ b ]indole derivatives 293b were produced.…”
Section: Synthetic Methodology Involving C–h Functionalization Alomentioning
confidence: 99%
“…Shi et al explored the reactivity of gem -diester substituted cyclopropenes 292 containing a pendant indole core on one of the Csp 2 atoms of the strained carbocycle ( Scheme 37 ) [ 114 ]. They uncovered a Lewis acid-catalyzed cycloisomerization reaction which outcome depended on the substitution of the second Csp 2 of the cyclopropene moiety: when it included a H atom azocino[5,4- b ]indoles 293a were obtained, however when it contained an aryl group tetracyclic (epiminoethano)cyclopenta[ b ]indole derivatives 293b were produced.…”
Section: Synthetic Methodology Involving C–h Functionalization Alomentioning
confidence: 99%
“…For the cyclopropenes 123 bearing an aryl group, a different reaction route was followed, and a kind of tetracyclic product, (epiminoethano)cyclopenta[ b ]indoles 124 were given in high yields (Scheme 21). 34…”
Section: Annulation Reactions Of Commonly Stable Cyclopropenesmentioning
confidence: 99%
“…158 Subsequently, Shi reported similar reactions using 3,3-diester substituted cyclopropenes 210 prepared from tryptamine derivatives. 159 These compounds in the presence of Brønsted acids evolved through an intramolecular Friedel−Crafts reaction including ring cleavage of three-membered ring to different scaffolds (Scheme 33A). The reaction outcome depended on the substitution at position 2 of the cyclopropene 210.…”
Section: Electrophilic Aromatic Substitution Reactions Using Cyclopro...mentioning
confidence: 99%
“…In 2015, they reported that monoester-substituted cyclopropenes decorated with pedant unprotected indoles could undergo metal-catalyzed cyclizations involving S E Ar reactions without cleaving the cyclopropane backbone . Subsequently, Shi reported similar reactions using 3,3-diester substituted cyclopropenes 210 prepared from tryptamine derivatives . These compounds in the presence of Brønsted acids evolved through an intramolecular Friedel–Crafts reaction including ring cleavage of three-membered ring to different scaffolds (Scheme A).…”
Section: Electrophilic Aromatic Substitution Reactions Using Cyclopro...mentioning
confidence: 99%